Cloning, Sequencing, and Expression of the Gene Encoding a Family 9 Cellulase from Bacillus licheniformis F11 in Escherichia coli and Bacillus megaterium, and Characterization of the Recombinant Enzymes - IS HELIANTI; MARIA ULFAH; NIKNIK NURHAYATI; LLINA MULYAWATI (Indonesian Society for microbiology, 2014)
A gene encoding cellulase belonging to the glycosyl hydrolase family 9 along with its native promoter was isolated from Bacillus licheniformis F11, cloned in Escherichia coli DH5 α and subcloned by transconjugation to Bacillus megaterium MS941. Functionality of the encoded protein was proven both in heterologous hosts, E. coli and B. megaterium. In the latter, the gene product was found in the extracellular fraction expressing a high specific activity; whereas in E. coli the protein was not secreted into the medium, and rather, showed a lower specific activity. The optimum temperature of the recombinant enzyme expressed in the hosts range from 65-75 ºC; whereas the optimum pH is 6. The recombinant enzyme was stable between 50-60 ºC and in a broad pH range (pH 5 - 9). Addition of Ca2+ and Fe3+ enhanced the enzyme activity, whereas EDTA and Cu2+ had the opposite effect. Lichenin, rather than carboxyl methyl cellulose, is the preferred substrate.